Science teaching for students with Autism Spectrum Disorder: what the national literature suggests (Research, Society and Development, 2022)
This article reports the results found in an integrative literature review on techniques and methodological procedures, currently used in Science Education (SE), in Brazil, for students diagnosed with Autism Spectrum Disorder (ASD). The research work consisted of searching, grouping, and analyzing scientific articles, according to previously established inclusion criteria. The articles were retrieved from electronic databases using the descriptors aligned with the general objective of the study. The problem that gave rise to the present research refers to the lack of investigations of this nature, conducted in Brazil and which aim to consolidate what is advocated by Evidence-Based Practice (EBP). The nine studies identified were published between 2016 and 2021, had non-experimental natures, involved students diagnosed with ASD, included in regular Elementary, Middle and High school settings, as well as Special Education environments. In this context, a variety of science contents was detected, including specific topics in Biology, Chemistry and Physics. The results of this review indicated the prevalence of simultaneously using different pedagogical strategies for teaching science, with emphasis on the use of visual resources, didactic games, and practical activities. Despite the research data reporting the positive effects of the implemented practices, these results must be interpreted with caution. Limited reference to the current international literature on EBP for CE associated with poor description of the teaching methods, participant characteristics as well as in the dependent variables under investigation were identified.